Labour Unionism and Workers Welfare in Nigeria - OKOLIE, Ugo Chuks (The Indonesian Journal of Social Studies, 2023)
This paper looks at the contributions worker unions have made to ensuring prompt promotions for workers, the regular delivery of training programs for workers, and the extent to which effective labour unionism has ensured the prompt payment of pensions and gratuities to retirees in Nigeria. The study's theoretical framework was the pluralism theory by Flanders and Fox (1970). Secondary sources were used to collect the data. On the produced materials, contextual analyses were conducted. The results of the study showed that due to the difficult political environment in the nation, Nigeria has not had effective unionism over the years. Because of this, it is uncommon for employer support employee welfare programs like job security, prompt promotion with commensurate financial benefits, regular training programs, and pension and gratuity benefits to be provided. All of these have caused employees across Nigerian government institutions to experience hunger, poverty, and a lack of motivation to carry out their assigned duties. The researcher suggested that labour unions in Nigeria, among other things, should persuade government institutions to ensure adequate provision of workers welfare in order to improve the socioeconomic wellbeing of the workers and toward higher performance in the organizations; unions should seek redress in industrial court with regards to any infringement on the rights of any worker in Nigeria as this has produced results in the past.